Translation and Communication. The Influence of Culture and Context in Danish and British Sales Brochures - Norlyk, Birgitte (HERMES - Journal of Language and Communication in Business, 1999)
Using a framework of culture and context, the present case study compares the English language version of a standardized sales brochure, produced in Denmark, to a culturally adapted brochure made especially for the British market. First, the analysis demon-strates the influence of cultural contexts on the concept of appropriate product settings. Second, the analysis illustrates how differences in coding and decoding processes influ-ence the stylistics of product descriptions and the choice of selling points in Denmark and in Britain.